Novel virtual satellite formation scheme for deterministic transmission - Chuan XU; Mi ZHOU; Guofeng ZHAO; Zhaojing CUI; Xiongwen HE (Tongxin xuebao)
Although satellite formation flying could effectively support deterministic transmission due to its stable formation, but its formation control required significant real-time computational overhead and did not support flexible deployment for multi-missions.Thus, based on the extensively deployed low-earth orbit (LEO) constellations, a virtual satellite formation scheme was proposed, which achieved deterministic transmission of time-sensitive mission by selecting appropriate satellites to form a formation.Firstly, the concept of virtual satellite formation was elaborated, and the challenges and performance requirements of virtual satellite formation based on LEO constellations were analyzed.Then, by characterizing the survival time and distance variation rate of inter satellite links (ISL), formation node selection mode was constructed, and a virtual satellite formation selection algorithm was designed to meet the requirements of time-sensitive missions.Finally, satellite network scenario was built to verify the proposed scheme by STK and Exata.Experimental results show that the proposed scheme can provide the same performance indicators as satellite formation flying for time-sensitive missions, while offering more flexibility in deployment.